Meningkatkan Kemampuan dan Niat Menulis Akademik Siswa melalui Pelatihan Menggunakan Mendeley - Faruq Alhasbi; Elina Intan Apriliani (Bulletin of Community Engagement, 2024)
In an effort to keep the age developments in the publication world up-to-date on accredited journals and international journals requires the author to write the article using mendeley's application. Writing articles and scientific works is essential to improving the quality and quality of the lecturer and of the student completing the final task in particular. Currently the student who wrote the scientific work, making the quotations and library lists was still manual and did not have the knowledge in using mendeley's application. The purpose of this community's devotion activity is to improve the ability and interest of the students in writing scientific works. The method used in the workshop activity is conducted with lecture on the materials understanding of the mendeley application, discussion and continued practice for participants for installation, account making to create sittings and references. Participants on this activity are students at the mamba 'ul ulum surakarta. The results of this workshop show increased student interest in scientific writing and also show that students are able to perform installations and are able to use mendeley's applications to create sitations, manage references, reference lists and climate Settings.